RETRACTED: The Impact of Quality of Governance, Renewable Energy and Foreign Direct Investment on Sustainable Development in Cee Countries - Simionescu, Mihaela; Szeles, Monica Răileanu; Gavurova, Beata; Mentel, Urszula (Frontiers in Environmental Science, 2021)
Recent debates in Environmental Kuznets Curve (EKC) in the context of European Green Deal highlights that pollution could be controlled using other channels than economic development. The renewable energy consumption role in reducing pollution should be correlated with quality of governance that could support or not the initiatives to a cleaner environment. This study considers the renewable Kuznets curve for ten Central and Eastern European countries in the period 2006-2019 using as control variables economic indicators (index of economic freedom, foreign direct investment, domestic credit to private sector and labour productivity) and indicators reflecting quality of governance (Worldwide Governance Indicators and Google Trends indexes associated to key-word corruption in each language). The research is based on two types of panel data models: panel dynamic OLS model (PDOLS) and panel autoregressive distributed lag models based on pooled mean group (PMG) estimator. The results indicated that government effectiveness reduces pollution in the short-run and in the long-run, while the control of corruption and rule of law supports environmental protection in the lung-run. Google searches for corruption as a proxy for quality of governance explain the GHG emissions with imediate and practical implications in nowcasting pollution.